Caprine Myostatin Gene Polymorphism in Domestic and Wild Goat Breeds in Duhok Province/Kurdistan Region of Iraq Using PCR-RFLP and SNP Markers - Abbas, Awat M.; Jubrael, Jaladet M.; Mohammed, Ahmed B. (Science Journal of University of Zakho, 2023)
In Iraq generally and Kurdistan region specifically, goats are an important resource for meat and milk production. It is well known that Myostatin genes (MSTN) have the essential role in growth and development due to its crucial involvement in muscle growth. The goal of this research was to reveal the polymorphism of MSTN gene in different Capra hircus breeds (native, Shami, Meriz and Kamori goat) and in wild mountain goat (Capra aegagrus) via PCR-RFLP technique and direct seqencing The MSTN (exon 1) polymorphisms were investigated in all breeds, MSTN-Dra I/RFLP revealed three genotypes AA and BB were homozygous and AB was heterozygous. The calculated genotype frequencies were 0.270, 0.368 and 0.362 for AA, BB and AB genotype respectively. The allelic frequency was 0.451 for the A allele and 0.549 for the B allele. The average of the observed heterozygosity was 0.362 and the observed homozygosity was 0.638. The sequence data of MSTN gene of Native and Shami goats revealed 31 SNPs in nonfunctional region. In addition, in exon region there was 1 SNPs in both breed samples which did not change amino acid sequence and its silence mutation.       In conclusion, the result of PCR-RFLP and SNP experiments obtained in this investigation were evaluated as very useful in genotype analysis of local goat breeds/populations. Thus, DNA polymorphisms in the Myostatin gene could be used as reliable genetic marker in breeding programs in this region.
Keywords: Capra aegagrus; (110) GaAs; (ITS) region primers; (311)B GaAs; -rigid ring; SNP